2021
DOI: 10.1101/2021.07.30.21261340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and feasibility of research lumbar puncture in Huntington’s disease: the HDClarity cohort and bioresource

Abstract: Background: Biomarkers are needed to monitor disease progression, target engagement and efficacy in Huntington's disease (HD). Cerebrospinal fluid (CSF) is an ideal medium to research such biomarkers due to its proximity to the brain. Objectives: To investigate the safety and feasibility of research lumbar punctures (LP) in HD. Methods: HDClarity (NCT02855476) is an ongoing international biofluid collection initiative built on the Enroll-HD platform, where clinical assessments are recorded. It aims to recruit … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The HDClarity study (NCT02855476) 5 is an ongoing, international, multi-site, longitudinal CSF collection initiative aiming to recruit 1200 participants. The primary objective is to collect high-quality CSF samples for the evaluation of biomarkers and pathways that will enable the development of novel treatments for HD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HDClarity study (NCT02855476) 5 is an ongoing, international, multi-site, longitudinal CSF collection initiative aiming to recruit 1200 participants. The primary objective is to collect high-quality CSF samples for the evaluation of biomarkers and pathways that will enable the development of novel treatments for HD.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Rodrigues et al 5 addressed for the first time the safety profile of LP in a cohort of patients with Huntington's disease and controls who took part in the largest CSF collection initiative, HDClarity. They found that the adverse events rate in their cohort was similar to that reported in other neurological diseases or the general population and that age, gender, BMI, and disease burden score (DBS), as a surrogate of disease status, did not show association with the rate of post LP headache.…”
Section: Introductionmentioning
confidence: 99%
“…CSF huntingtin quantification remains limited by the sensitivity of current mHTT assays -many far from clinical motor onset individuals have unquantifiably low levels 11,99 , making therapeutic lowering difficult to assess; and the difficulty of quantifying wtHTT either independently or through inference from the total HTT level based on current assays 100 . More broadly, the HD biomarker field lacks well-powered replication studies, but the HDClarity bioresource has a large and expanding CSF and plasma collection for this purpose 101 .…”
Section: Biofluidsmentioning
confidence: 99%